Waste sodium-ion battery hard carbon material recycling method based on water-based solution and application of waste sodium-ion battery hard carbon material recycling method

Through water-based solution treatment and annealing technology, the problem of recycling and regeneration of hard carbon materials for waste sodium ion batteries is solved, efficient, environmentally friendly and economical resource recycling is achieved, and the performance and recovery rate of hard carbon materials are improved.

CN119637840AInactive Publication Date: 2025-03-18ZHEJIANG UNIV

Patent Information

Application Number
CN202411600034.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently recycle and regenerate hard carbon materials in waste sodium ion batteries, and the recycling process is complex and energy consumption is high, which affects environmental protection and economic benefits.

Method used

Using water-based solution treatment and annealing technology, the side reaction products on the surface of hard carbon negative electrode powder are removed by dismantling and separating waste sodium ion batteries, and the primary regenerated hard carbon material is obtained by solid-liquid separation, washing and drying, and its performance is improved through annealing treatment.

Benefits of technology

The performance of failed hard carbon materials has been significantly restored, and the reuse of low-cost and environmentally friendly waste sodium ion battery hard carbon materials has been achieved, reducing the demand for new materials, and reducing resource waste and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637840A_ABST
    Figure CN119637840A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of waste sodium-ion battery recovery, and discloses a water-based solution-based waste sodium-ion battery hard carbon material recovery and regeneration method and application of the water-based solution-based waste sodium-ion battery hard carbon material recovery and regeneration method. Comprising the following steps: disassembling and separating the waste sodium-ion battery to obtain a hard carbon negative pole piece; stripping the hard carbon active material from the surface of the current collector, and collecting hard carbon negative electrode powder in the waste battery; removing side reaction products on the surface of the hard carbon negative electrode powder by adopting a water-based solution treatment method, and carrying out solid-liquid separation, washing and drying to obtain a primary regenerated hard carbon material; according to the specific failure mechanism and failure degree of the hard carbon material in the battery, the primary regenerated hard carbon is further subjected to annealing treatment, and the high-performance value-added recycled hard carbon material is obtained. The method adopts a water-based solution recovery technology, and has the advantages of safety, environmental protection and low cost; and meanwhile, the recovery process is simple, convenient and feasible, and has higher economic benefits. The performance of the regenerated hard carbon material is remarkably recovered, and the regenerated hard carbon material can be reused for manufacturing the sodium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waste ion battery recycling, and specifically relates to a method for recycling and regenerating hard carbon negative electrode materials of waste sodium ion batteries based on a water-based solution and an application thereof. Background Art

[0002] Sodium-ion battery (SIB) is an energy storage technology that has attracted much attention in recent years. As a potential alternative to lithium-ion batteries, it has shown great application prospects in fields such as energy storage and electric transportation due to its abundant resources, low cost and environmental friendliness. However, both sodium-ion batteries and lithium-ion batteries will experience a decrease in capacity and eventually become scrapped after a period of use. Lithium / sodium-ion batteries contain a large amount of harmful substances, and improper disposal can cause serious damage to the environment. Therefore, the development of efficient recycling technology has become the key to the sustainable development of the lithium / sodium battery industry.

[0003] Currently, the most common methods for extracting high-value materials from spent lithium-ion batteries are pyrometallurgy and hydrometallurgy, while direct recycling technology has also attracted increasing attention due to its environmental friendliness. Zhang et al. [1] The application of hydrometallurgy in the recycling of lithium-ion batteries was studied, especially the leaching of metal components (such as lithium, cobalt, nickel) by acid solutions (such as sulfuric acid and hydrochloric acid), and then the recovery of metals by precipitation and extraction. Hydrometallurgy is widely used in industry due to its high recovery rate and suitability for large-scale processing. Huang et al. [2] proposed a pyrometallurgical method, which separates metals by high-temperature melting. This method is suitable for processing the metal components of waste batteries, especially cobalt and nickel. However, pyrometallurgy is not effective in recovering lithium, and it consumes a lot of energy and has serious pollution problems. Li et al. [3] The study mentioned that direct recycling technology can reuse waste lithium battery materials in battery manufacturing through simple repair or reprocessing. This method avoids the complete decomposition of battery materials, so in theory it can save a lot of resources and energy, especially for batteries with a short lifespan, but the technical means are complex and the process needs to be optimized.

[0004] Similarly, the recycling methods of spent sodium-ion batteries mainly include pyrometallurgy, hydrometallurgy and biometallurgy, and the majority of the recycled objects are positive electrode materials. Li et al. [4]A process for regenerating waste sodium-ion battery positive electrode materials by heat treatment is reported. Heat treatment can remove pollutants on the surface of the material and restore the electrochemical properties of the positive electrode material. The regenerated positive electrode material can be directly used in the manufacture of new batteries, reducing the demand for raw materials, but the recycling process is relatively complicated and energy-intensive. The patent with publication number CN118231824A proposes a method for regenerating positive electrode materials by utilizing hydrothermal reaction and providing a sodium source, but the energy consumption of the recycling process is relatively high. The patent with publication number CN114229875A proposes a hydrometallurgical process for leaching metal elements using a multi-step solution, but this method is not only complex in process and energy-intensive, but also environmentally unfriendly and has a low recovery rate.

[0005] As the most widely used negative electrode material for sodium ion batteries, hard carbon has a high recycling value. First, compared with graphite at 30,000-60,000 yuan / ton, the general price of hard carbon negative electrode materials is usually 200,000-400,000 yuan / ton, and the price of hard carbon with high performance and high energy density has reached 700,000-1 million yuan / ton. Recycling hard carbon materials can reduce the demand for new materials, thereby saving resources and reducing production costs; secondly, recycling hard carbon materials can reduce harmful substances in waste batteries, reduce their negative impact on the environment, help to achieve the recycling of materials, reduce the waste of non-renewable resources, and promote sustainable development. At present, there is a lack of research on the recycling of hard carbon materials for sodium ion batteries. The patent with publication number CN115058598A proposes to transfer sodium from the positive electrode of waste batteries to the hard carbon negative electrode through an electrochemical transfer method to achieve the separation of sodium and other metal elements in the positive electrode of waste sodium ion batteries, and then separate sodium from hard carbon by adding oxalic acid solution. However, this method emphasizes recycling, and it does not explain whether the performance of hard carbon after recycling is restored. The patent with publication number CN118630354A proposes to effectively wet, emulsify and disperse the powder on the surface of the negative electrode material through a weak alkaline mixed solvent to achieve the separation of the hard carbon powder and the current collector, but this method also only focuses on the recovery efficiency of the powder and the current collector, and does not test the electrochemical performance of the recovered hard carbon powder. Therefore, it is urgent to develop a set of economical and efficient methods for recycling and regenerating hard carbon materials for sodium ion batteries to achieve the recycling of high-performance hard carbon materials. This provides important technical guarantees for further reducing the cost of sodium ion batteries and promoting the sustainable development and large-scale application of sodium ion batteries.

[0006] References

[0007] [1]Li L., Zhang

[0008] [2]Huang B.,Pan Z.,et al.Recycling of lithium-ion batteries:Recentadvances and perspectives[J].Journal of Power Sources,2018,249,317-328.

[0009] [3]Li,L.,Zhang,X.,Li,M.,Chen,R.,Wu,F.,Amine,K.,et al.Directregeneration of spent LiCoO 2 cathodes from lithium-ion batteries[J].NatureSustainability,2019,2(3),220-227.

[0010] [4]Li,Y.,Zhao,L.,Wang,J.,et al.Thermal regeneration of spent sodium-ion battery cathode materials for reuse in new batteries[J].Journal of PowerSources,2020,451,227778. Summary of the invention

[0011] The present invention proposes a highly efficient recovery and regeneration method for hard carbon materials in waste sodium ion batteries. The present invention adopts water-based solution treatment and annealing technology, which can not only significantly restore the performance of failed hard carbon materials, but also achieve the reuse of hard carbon materials in waste sodium ion batteries in a low-cost and environmentally friendly manner. The regenerated hard carbon materials can be used to manufacture new sodium ion batteries, thereby achieving resource recycling, and has high industrial application prospects and economic benefits.

[0012] The core of the present invention is to use a water-based solution method to recycle hard carbon materials in waste sodium-ion batteries. The specific process includes: disassembling and separating waste sodium-ion batteries, collecting hard carbon negative electrode powder, and then using a water-based solution to remove side reaction products on the surface of the hard carbon negative electrode powder, and obtaining primary regenerated hard carbon materials through solid-liquid separation, washing and drying. According to the mechanism and degree of failure of the hard carbon material in the battery, the primary regenerated material is further annealed to improve its performance, and finally a high-performance value-added recycled hard carbon material is obtained.

[0013] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions.

[0014] In a first aspect of the present application, a method for recycling and regenerating hard carbon materials from waste sodium ion batteries based on a water-based solution is provided. According to a specific example of the present invention, the specific steps are as follows:

[0015] (1) dismantling and separating the waste sodium ion batteries in a discharged state to obtain hard carbon negative electrode sheets, stripping the hard carbon active materials from the current collector, and collecting the hard carbon negative electrode powder in the waste batteries;

[0016] (2) mixing the hard carbon negative electrode powder with a water-based solution for treatment, and obtaining a primary regenerated hard carbon material through solid-liquid separation, washing, and drying;

[0017] (3) The primary regenerated hard carbon material is further annealed to obtain a high-performance value-added recycled hard carbon material.

[0018] In the above technical solution, further,

[0019] In step (2):

[0020] The water-based solution has a pH of 1-12, and can be a combination of one or more aqueous solvents selected from deionized water, acid solution, hydrolyzed salt solution with adjustable solution pH, and ligands that can be combined with transition metal ions. The flexible combination of the water-based solution treatment with different pH ranges, the selection of acid solution, the hydrolyzed salt solution with adjustable pH value, and the use of ligands specifically disclosed in the present invention can be customized for different waste sodium ion battery positive and negative electrode material systems and failure mechanisms to achieve the best recovery effect. For example, the water-based solution used is determined based on the type and content of the dissolution of the positive electrode transition metal deposited on the surface of the failed hard carbon negative electrode material. The acid solution is selected from one or more of inorganic acids and organic acids, the inorganic acids include but are not limited to hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, carbonic acid, boric acid, and hydrofluoric acid, and the organic acids include but are not limited to formic acid, acetic acid, oxalic acid, citric acid, tartaric acid, alginic acid, and amino acids; the hydrolyzed salt solution with adjustable solution pH is selected from one or more of strong acid and weak base salts and strong base and weak base acid salts, the strong acid and weak base salts include but are not limited to ammonium sulfide, ammonium sulfate, ammonium nitrate, ammonium phosphate, ammonium fluoride, and ferrous sulfate, and the strong base and weak base acid salts include but are not limited to sodium acetate and sodium carbonate; the ligand is selected from one or more of water-soluble chelating agents and complexing agents, including but not limited to ethylenediaminetetraacetic acid (EDTA), bis(aminovinyl)phosphoric acid (DTPA), hydroxyethylenediaminetriacetic acid (HEDTA), and polyvinyl sulfonic acid (PVS).

[0021] Ultrasound, mechanical stirring or heating can be used to accelerate the treatment process in the water-based solution process, and the time is 0.1-24 hours; the primary regenerated hard carbon negative electrode material is obtained by conventional solid-liquid separation, washing and drying methods in the industry. The drying temperature is usually 25℃-200℃, and the drying time is usually 0.5-12 hours.

[0022] In step (3):

[0023] The annealing method includes using a carbonization furnace or plasma heating. The primary regenerated hard carbon material is heat treated using a carbonization furnace or plasma heating method to obtain a high-performance regenerated hard carbon material. Further, the conventional carbonization furnace annealing temperature is 300-1200°C, and the treatment time is 0.01-2 hours; the plasma heating treatment temperature is 1000-1600°C, the heating rate is 500-1000°C / minute, and the heating time is 1-30 seconds.

[0024] The second aspect of the present invention provides a method for preparing a negative electrode plate of a sodium ion battery using a recycled hard carbon material, wherein the recycled hard carbon negative electrode material (which may be the primary regenerated hard carbon material or the recycled hard carbon material obtained after annealing, collectively referred to as regenerated hard carbon) is reused in the manufacture of a sodium ion battery. The negative electrode active material of the sodium ion battery is a recycled hard carbon or a composite material containing recycled hard carbon. The specific electrode plate preparation process includes but is not limited to the following steps: copper foil or aluminum foil is used as a current collector, the active material in the negative electrode slurry includes a recycled hard carbon material, and the mass proportion of the active material is 70%-98%; the proportion of conductive carbon black is 1%-20%; the binder includes one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and sodium alginate (SA), and the mass proportion is 1%-10%.

[0025] Compared with the prior art, the present invention has the following outstanding features and beneficial effects:

[0026] (1) Environmental friendliness: Traditional recycling methods mostly use organic solvents, which are not only costly but also pollute the environment. In contrast, water-based methods use water as a solvent, which reduces the use of harmful chemicals, is more environmentally friendly, and is in line with the concept of green chemistry.

[0027] (2) Simple and efficient process: Water-based recycling technology is usually simple to operate, does not require complex equipment or high-pressure conditions, and can effectively reduce energy consumption and costs. This method can quickly and efficiently recover hard carbon materials through simple steps such as dissolving electrolytes and separating electrode materials, while maintaining the structural integrity of hard carbon negative electrode materials.

[0028] (3) High cost-effectiveness: The water-based solution method significantly reduces the cost of the recycling process due to the use of cheap water and conventional equipment. At the same time, this method does not rely on expensive chemical reagents and is suitable for large-scale industrial applications. (4) High recovery rate and performance retention of hard carbon materials: The water-based method can maintain the structure and electrochemical properties of hard carbon materials and reduce damage to their microstructure during the recycling process. Hard carbon has excellent sodium storage properties as a negative electrode material, and the water-based recovery method can better maintain these properties and ensure the efficient reuse of recycled materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The XRD diagrams of Examples 1, 2, 4 of the present invention, the original hard carbon material and Comparative Examples 1 and 2 are shown.

[0030] Figure 2 1 and 2 are Raman spectra of Examples 2 and 4 of the present invention and the original hard carbon material.

[0031] Figure 3These are SEM images of Examples 1, 2, 4 of the present invention, the original hard carbon material, and Comparative Examples 1 and 2.

[0032] Figure 4 0.1C first cycle charge and discharge curves of Examples 1-4 of the present invention, the original hard carbon negative electrode, and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0033] The present invention will be described clearly and completely below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented according to the technical solution of the present invention, and provides a detailed implementation method and a specific operation process. Obviously, the described embodiments are part of the embodiments of this application, rather than the embodiments described in all the embodiments, and the protection scope of the present invention is not limited to the following embodiments.

[0034] The sources of the raw materials and instruments used in the examples are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0035] In an embodiment of the present invention, the regenerated hard carbon material is made into a negative electrode plate for a sodium ion battery. The specific preparation steps are as follows. It should be noted that the preparation of the regenerated hard carbon negative electrode plate is not limited to the following steps:

[0036] (1) Preparation of slurry: Active material, Super P and polyvinylidene fluoride (PVDF) in a mass ratio of 90:5:5 were weighed into a stirring box containing N-methylpyrrolidone (NMP) solvent, and mixed by a high-speed stirrer to obtain a uniform electrode slurry.

[0037] (2) Coating and drying: The slurry was coated on copper foil, dried at 50°C, and punched into 12 mm diameter disc electrodes with a loading of 2.0-3.5 mg / cm 2 , and then the electrode sheet was vacuum dried at 120°C for 10 hours.

[0038] In this embodiment, the battery was assembled and tested by the following method: the dried regenerated hard carbon electrode was transferred to a glove box filled with high-purity argon gas, and the half-cell was assembled with metallic sodium as the counter electrode, Whatman GF / F glass fiber as the diaphragm, and 1M NaPF 6 EC-DEC (ethylene carbonate-diethyl carbonate) is the electrolyte for assembling CR2032 button half-cell. The battery test method is as follows:

[0039] With 300mAh g -1 The nominal specific capacity of the hard carbon negative electrode was tested for 0.1C charge and discharge with a voltage range of 0.005-2V.

[0040] The present invention is further described below by way of examples.

[0041] Example 1 A method for recycling and regenerating a hard carbon negative electrode of a waste sodium ion battery based on a water-based solution, the specific steps are as follows:

[0042] (1) disassembling and separating the used sodium ion batteries in a discharged state to obtain hard carbon negative electrode sheets;

[0043] (2) 2 g of hard carbon negative electrode sheet was mixed with 50 mL of hydrochloric acid solution with a pH of 5, and the active material hard carbon was peeled off from the current collector; the aqueous solution containing hard carbon powder was ultrasonicated for 0.5 h, and then solid-liquid separation was performed by filtration, the hard carbon powder was collected and washed with deionized water, and then dried at 80° C. for 12 hours to obtain a primary regenerated hard carbon material;

[0044] (3) Weigh 1 g of primary regenerated hard carbon material into an alumina crucible, place it in a tubular furnace, and heat it to 1000°C at 3°C / min under an argon atmosphere. After keeping it at this temperature for 2 hours, cool it naturally to obtain a high-performance regenerated hard carbon material.

[0045] Example 2

[0046] The difference between this embodiment and embodiment 1 is that in step 2, 2 g of hard carbon material is mixed with 50 mL of nitric acid solution with pH=5, and the other steps are the same as those in embodiment 1.

[0047] Example 3

[0048] The difference between this embodiment and embodiment 1 is that in step 2, 2 g of hard carbon material is mixed with 50 mL of 0.5% by mass ammonium chloride solution, and the other steps are the same as those in embodiment 1.

[0049] Example 4

[0050] The difference between this embodiment and embodiment 2 is that in step 3, the heat treatment method is specifically: using a plasma heating method to increase the temperature to 1200°C at a heating rate of 900°C / min for 10 seconds, and the other steps are the same as in embodiment 2.

[0051] Original hard carbon

[0052] The original uncirculated hard carbon material was used as the negative electrode material, and the original hard carbon negative electrode was prepared using the above-mentioned sodium ion battery negative electrode sheet preparation steps and tested.

[0053] Comparative Example 1

[0054] In this comparative example, the waste sodium ion batteries in a discharged state are disassembled and separated to obtain hard carbon negative electrode sheets; and the unregenerated hard carbon negative electrode sheets are directly used to assemble button half-cells.

[0055] Comparative Example 2

[0056] The difference between this comparative example and Example 1 is that the annealing treatment in step 3 is not performed, but the primary regenerated hard carbon material obtained in step 2 is directly used for the preparation of the negative electrode sheet of the sodium ion battery and tested.

[0057] The following is an analysis using the test results of Examples 1, 2, 4, original hard carbon, and Comparative Examples 1 and 2 as specific examples. The test results of other examples are equivalent to those of Examples 1, 2, and 4.

[0058] The XRD test results of Examples 1, 2, 4, original hard carbon and Comparative Examples 1 and 2 are as follows: Figure 1 As shown, it can be seen that the hard carbon negative electrode of comparative example 1 has an obvious (110) diffraction peak, indicating that there is obvious sodium precipitation on the surface of the hard carbon negative electrode of comparative example 1; while the sodium metal peak of the hard carbon materials of examples 2 and 4 disappears, and their structures are basically consistent with the original hard carbon materials, indicating that the structure of the regenerated hard carbon material is basically restored. Since the by-products generated during the cycle are some amorphous compounds, the XRD results of comparative example 2 are also similar to those of the original hard carbon.

[0059] The Raman test results of Examples 2 and 4 and the original hard carbon are as follows: Figure 2 As shown, it can be seen that the Raman absorption peaks of Examples 2 and 4 are consistent with the Raman absorption peaks of the original hard carbon material, which further illustrates that the structure of the regenerated hard carbon material of Examples 2 and 4 is restored.

[0060] The SEM test results of Examples 1, 2, 4, the original hard carbon and Comparative Examples 1 and 2 are as follows: Figure 3 As shown, it can be seen that the sodium precipitation phenomenon on the surface of Examples 1, 2 and 4 completely disappears, and the by-products generated during the circulation process are also decomposed due to the annealing treatment. Their appearance morphology is basically consistent with that of the original hard carbon material, indicating that the morphology of the regenerated hard carbon material is basically restored.

[0061] The first cycle 0.1C charge and discharge test results of Examples 1-4, original hard carbon and Comparative Examples 1 and 2 are as follows: Figure 4 As shown in the figure, it can be seen that compared with comparative example 1, the reversible capacities of Examples 1-4 have been greatly improved, and the first-cycle reversible capacities of Examples 1 and 2 have even recovered to about 90% of the first-cycle reversible capacity of the original hard carbon. Compared with Example 1, the first-cycle reversible capacity of comparative example 2 without annealing treatment is only 74.8 mAh g -1 , which is much lower than that of Example 1. Table 1 lists the first cycle reversible capacities of various examples and comparative examples in detail.

[0062] Table 1 Electrochemical performance of examples

[0063]

[0064]

[0065] The above are only some preferred embodiments of the present invention, and the present invention is not limited to the above embodiments, nor does it limit the protection scope of the present invention. Any modification, replacement, improvement, etc. derived from the concept of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for recycling and regenerating hard carbon materials from waste sodium ion batteries based on a water-based solution, characterized in that: include: Hard carbon negative electrode powder from waste sodium ion batteries is collected, and side reaction products on the surface of the hard carbon negative electrode powder are removed by a water-based solution treatment method. Primary regenerated hard carbon material is obtained through solid-liquid separation, washing and drying. The primary regenerated hard carbon material is further annealed to obtain high-performance value-added recycled hard carbon material.

2. The method for recycling and regenerating hard carbon materials from waste sodium ion batteries based on a water-based solution according to claim 1, characterized in that: The water-based solution has a pH range of 1-12 and is selected from one or more components of deionized water, acid solution, hydrolyzed salt solution with adjustable pH value, and a ligand capable of combining with transition metal ions.

3. The method for recycling and regenerating hard carbon materials from waste sodium ion batteries based on a water-based solution according to claim 2, characterized in that: The acid solution is selected from one or more of inorganic acids and organic acids. The inorganic acids include but are not limited to hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, carbonic acid, boric acid, and hydrofluoric acid. The organic acids include but are not limited to formic acid, acetic acid, oxalic acid, citric acid, tartaric acid, alginic acid, and amino acids.

4. The method for recycling and regenerating hard carbon materials from waste sodium ion batteries based on a water-based solution according to claim 2, characterized in that: The hydrolysis salt solution capable of regulating the pH of the solution is selected from one or more of strong acid and weak base salts and strong base and weak acid salts. The strong acid and weak base salts include but are not limited to ammonium sulfide, ammonium sulfate, ammonium nitrate, ammonium phosphate, ammonium fluoride, and ferrous sulfate. The strong base and weak acid salts include but are not limited to sodium acetate and sodium carbonate.

5. The method for recycling and regenerating hard carbon materials from waste sodium ion batteries based on a water-based solution according to claim 2, characterized in that: The ligand is selected from one or more water-soluble chelating agents and complexing agents, including but not limited to ethylenediaminetetraacetic acid (EDTA), bis(aminovinyl)phosphoric acid (DTPA), hydroxyethylenediaminetriacetic acid (HEDTA), and polyvinyl sulfonic acid (PVS).

6. The method for recycling and regenerating hard carbon materials from waste sodium ion batteries based on a water-based solution according to claim 1, characterized in that: The water-based solution treatment method is to add the hard carbon negative electrode powder into the water-based solution, and ultrasound, mechanical stirring or heating can be used to accelerate the treatment during the process, and the treatment time is 0.1-24 hours; then the solid-liquid separation is carried out, and then the washing and drying are carried out, and the washing agent is deionized water or a mixed solution of water, ethanol and acetone; the drying temperature is 25°C-200°C, and the drying time is 0.5-12 hours, and finally the primary regenerated hard carbon material is obtained.

7. The method for recycling and regenerating hard carbon materials from waste sodium ion batteries based on a water-based solution according to claim 1, characterized in that: The annealing treatment is to use a carbonization furnace or a plasma heating method to heat treat the primary regenerated hard carbon material to obtain a high-performance regenerated hard carbon material; the carbonization furnace annealing temperature is 300-1200°C, and the treatment time is 0.01-2 hours; the plasma heating treatment temperature is 1000-1600°C, the heating rate is 500-1000°C / minute, and the heating time is 1-30 seconds.

8. A sodium ion battery regenerated hard carbon negative electrode material, characterized in that: The invention comprises a primary regenerated hard carbon material or a high-performance regenerated hard carbon material obtained by the method according to any one of claims 1 to 7.

9. A sodium ion battery negative electrode, characterized in that: It uses copper foil or aluminum foil as the current collector, the active material in the negative electrode slurry includes the regenerated hard carbon negative electrode material as described in claim 8, the mass proportion of the active material in the slurry is 70%-98%, the mass proportion of conductive carbon black is 1%-20%, and the binder is one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), styrene-butadiene rubber (SBR), sodium alginate (SA), and the mass proportion is 1%-10%.

10. A sodium ion battery, characterized in that: Contains the negative electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Comprehensive recovery method of waste sodium-ion battery

    CN114229875A

  • Recycling method of waste sodium-ion battery

    CN115058598A

  • Recycling method and application of waste sodium-ion battery positive electrode material

    CN118231824A

  • Sodium ion battery negative pole piece recovery method

    CN118630354A

  • Method for recycling high purity carbon material from waste lithium ion battery

    CN102709621A

Cited By

  • Method for rapidly preparing lithium and sodium ion battery negative electrode from waste sodium electrode plate

    CN120933525A